Two‐year outcomes in patients with mild refractory angina treated with enhanced external counterpulsation - Lawson, William E. (Clin Cardiol, 2006)
Background: In the International Enhanced External Counterpulsation Patient Registry (IEPR), approximately 85% of the patients treated are in Canadian Cardiovascular Society (CCS) class III‐IV with no option for further invasive coronary revascularization procedures. Hypothesis: This study sought to determine whether it is clinically important to establish whether the observed durable reduction in disabling severe angina with enhanced external counterpulsation (EECP) treatment can be extended to those with less severe CCS class II angina, who also have no option for further revascularization. Methods: This study evaluated the immediate response, durability and clinical events over a 2‐year period after EECP treatment in 112 patients with Canadian Cardiovascular Society (CCS) class II angina versus 1,346 patients with class III‐IV angina using data from the International EECP Patient Registry (IEPR). Results: Treatment with EECP significantly (by at least one CCS class) reduced angina frequency, nitroglycerinuse, and improved quality of life in both groups. At 2‐yearfollow‐up, 74% of class II and 70% of class III‐IV patients remained free of major adverse cardiovascular events (MACE) and continued to demonstrate a durable CCS class improvement over baseline. Conclusion: The robust effectiveness of EECP as a noninvasive device, together with its relatively low start‐up and recurrent costs, makes it an attractive consideration for treating patients with milder refractory angina in addition to the patient with severely disabling angina treated in current practice.